Granulomatous infection of the hand and wrist due to Azospirillum spp. - Serelis, John; Papaparaskevas, Joseph; Stathi, Angeliki; Sawides, Alexander L; Karagouni, Amalia D; Tsakris, Athanassios; Pangalis, Anastasia (Diagn Microbiol Infect Dis, 2013)
We report a case of Azospirillum infection manifestating as granulomatous tenosynovitis of the right hand, in an immunocompetent middle-aged female. We highlight the unusual source of the infection, the diagnostic workup, as well as the treatment approach.
Keywords: Anti-Bacterial Agents; Azospirillum; Clarithromycin; Female; Gram-Negative Bacterial Infections; Granuloma; Humans; Microbial Sensitivity Tests; Middle Aged; Tenosynovitis; Wrist